HYDROCEPHALUS AFTER NEONATAL MENINGITIS, CAUSED BY BACTERIUM LISTERIA MONOCYTOGENES ‒ A CASE REPORT - Tina Perme (Slovenska pediatrija)

(untitled)
Listeria monocytogenes is a facultative anaerobic bacterium that causes severe infection in neonates, immunocompro-mised patients and the elderly and is particularly dangerous for pregnant women. In the case of vertical transmission, there is an 80 % chance of spontaneous abortion, stillbirth or premature birth. Severe septicaemia and meningitis can occur in newborns, resulting in high morbidity and mortality. Here we present the case of a premature baby girl with a congenital Listeria infection and subsequent meningitis and postinfectious hydrocephalus. Neonatal meningitis caused by Listeria monocytogenes is rare but can lead to hydrocephalus and damage to the brain parenchyma. If an infection is suspected in a newborn, immediate empirical antibiotic treatment is necessary. The head circumference and condition of the ventricular system must be monitored and immediate neurosurgical intervention should be sought to limit further damage to the brain parenchyma and minimise the neurological consequences of the infection.